Fertility, Migration, and Spatial Interaction in Turkey: An Analysis under the Selectivity Hypothesis - Sibel Selim; Derya Bilgin (Coğrafya Dergisi)
Migration is a process of displacement, and it affects societies socially, economically, and structurally. This study gauges the impact of migration on fertility in Turkey. The evaluation is conducted in consideration of the selectivity hypothesis based on the Robust Poisson model. The data obtained from the 2013 Turkey Demographic and Health Survey were analyzed for this purpose. Not considering the role of social norms and one’s neighborhood relations while evaluating the relationship between variables prevents a holistic perspective; thus, the aspect of spatial interaction is taken into account in this study. The findings suggest that the variables that tend to significantly affect the fertility behaviors of women do not have an impact on the fertility behaviors of women having migrated from urban to rural areas. While variables such as age, education, employment status and household welfare have a significant effect on the fertility behaviors of women who migrated from rural areas to the cities as well as women residing in cities, the effect of these variables on fertility in rural areas is much higher. In this context, the study unveils a spatial relationship between migration and fertility in Turkey and, thus, invalidates the selectivity hypothesis.